Fuel Economy Improvement Analysis of Hybrid Electric Vehicle - Chung, In Chun; Kang, Hyehyun; Park, Jinil; Lee, Jonghwa (International Journal of Automotive Technology, 2019)
Owing to stricter environmental regulations and greenhouse gas reduction targets, hybrid electric vehicles (HEVs) have marked a remarkable increase in market share to replace internal combustion engine vehicles (ICEVs). Among HEVs, powersplit HEVs have attracted increasingly higher interest, and lead the trend of the HEV market. Although many studies have attempted to improve the fuel efficiency of powersplit HEVs, only a few studies have focused on the effect of vehicle system on fuel efficiency. Thus, this study compared the performance of a powersplit HEV and an ICEV by measuring and analyzing the improvement of fuel efficiency for each influencing factor. The energy flow in the main system components of a powersplit HEV, such as engine, motor, drivetrain, and wheel, was modeled, and four driving modes of ICEV and powersplit HEV were tested by using a chassis dynamometer. Finally, the improvement in fuel efficiency of a powersplit HEV was determined for each component and was quantified to allow comparative evaluation against that of an ICEV.
Keywords: Chassis dynamometers; Comparative evaluations; Energy flow; Greenhouse gas reductions; Hybrid electric vehicles (HEVs); Improvement analysis; Internal combustion engine vehicles; Vehicle energy; Energy flow; Fuel economy; Hybrid Electric Vehicle (HEV); Vehicle energy management